The Effectiveness of a Training Program based on Science Fiction Stories in Developing Creative Thinking and Problem Solving Skills for Basic–Stage Teachers - Al- Abed , Suad (Dirasat: Educational Sciences, 2020)
This study aims at investigating the effectiveness of a training program based on science fiction stories in developing creative thinking skills and problem solving for basic–stage teachers, where the sample of the study consisted of (76) male and female teachers from public schools in Bethlehem Directorate of Education. The sample of the study was distributed randomly into two groups: experimental control groups. The criterion – referenced test: creative thinking skills and problem solving test was applied. The reliability of the tests was conducted using Cronabach alpha. The training program was prepared and based on science fiction stories. The experimental group attended a training program based on science fiction stories, while the control group did not attend the training program. Treatment lasted for seven weeks. Results revealed that there was a statistically significant difference pertaining to using the training program in developing creative thinking skills and problem-solving in favor of the experimental group. The study recommends that teachers should be trained by having in-service training sessions in using science fiction stories to increase their creative thinking and problem-solving skills.